1989
DOI: 10.1161/01.cir.79.3.687
|View full text |Cite
|
Sign up to set email alerts
|

Effect of acute volume load on refractoriness and arrhythmia development in isolated, chronically infarcted canine hearts.

Abstract: In normal isolated, perfused canine ventricles, increased ventricular volume leads to shortening of refractoriness. To test the hypothesis that myocardium within an infarction zone is more susceptible to volume-induced changes in refractoriness than is normal myocardium, we measured strength-interval curves at low and high end-diastolic volumes at control and infarcted sites in 14 isolated, blood perfused, canine hearts with chronic (> 25 days) infarctions. In addition, the effect of volume load on inducing ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
18
0
2

Year Published

1992
1992
2015
2015

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(20 citation statements)
references
References 39 publications
0
18
0
2
Order By: Relevance
“…Moreover, Josephson 41 revealed that arrhythmias are often initiated from these borders. Calkins et al 8 observed that ventricular dilation shortens the refractoriness of the surviving myocardium in the infarct area rather than the healthy myocardium. Taken together, the following scenario is conceivable.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Josephson 41 revealed that arrhythmias are often initiated from these borders. Calkins et al 8 observed that ventricular dilation shortens the refractoriness of the surviving myocardium in the infarct area rather than the healthy myocardium. Taken together, the following scenario is conceivable.…”
Section: Discussionmentioning
confidence: 99%
“…cardiac electrophysiology; mechanical stretch; Fourier analysis STRETCH induces the modulation of electrical and mechanical activity in myocytes. The modulation of electrical activity, also referred to as mechanoelectrical feedback (14,35), includes the depolarization of the resting potential (2,17,21,27,28,31,70), alterations of the shape and duration of action potentials (3,11,21,27,28,31,47,57,70), changes in refractoriness (4,7,9,11,27,36,47,48), and the induction of afterdepolarizations (16,18,34). These electrophysiological changes have been related to the generation of different types of cardiac arrhythmias (7, 9, 13-15, 24, 26, 35, 40, 47).…”
mentioning
confidence: 99%
“…The electrophysiological effects of augmented load have been primarily studied under 2 disparate conditions, ie, during transient stretch (typically Յ50 ms) 1 or steady-state increases in stretch (volume). 2,3 The mechanism underlying the electrophysiological phenomena associated with transient stretch is thought to be related to cardiac mechanosensitive or stretch-activated channels. 4,5 Activation of these channels during diastole results in an inward or depolarizing current, either prolonging action potential duration (APD) or giving rise to an afterdepolarization.…”
mentioning
confidence: 99%
“…Increments in ventricular load that occur gradually and are sustained over time are associated with an increase in electrical excitability and shortening of refractoriness due to a parallel decrease in APD. 2,3,6 The cellular mechanism responsible for this form of mechanoelectrical coupling is generally unknown but has also been attributed to stretch-activated channels. 7,8 We hypothesized that an alternative mechanism was responsible for this phenomenon and was related to load-mediated activation of the ␤-adrenergic receptor (␤-AR), which in turn activates a catecholamine-sensitive K ϩ repolarization current.…”
mentioning
confidence: 99%